Analysis on the chemical spectra of Acrea terpsicore, Linnaeus, 1758 and Parantica aglea, Stoll, 1782 (Lepidoptera, Nymphalidae) wing scales - Thaj, Amina; Prasad, G. (ENTOMON, 2026)
The wing scale chemical spectra of two nymphalid species, Parantica aglea and Acrea terpsicore was investigated using Fourier Transform Infrared Spectroscopy (FTIR) to determine characteristic functional groups. Comparative analysis of the functional groups revealed the presence of several major groups, including alcohols, phenols, aldehydes, alkanes, alkenes, alkyl halides, alkynes, methylene, acids, nitro compounds, primary, secondary, and tertiary amines, esters, ethers, polysulfides, aryl disulfides, cyanide and thiocyanate ions, carbonate ions, organic sulphates, organic nitrates, nitrate ions, aromatic ethers, aromatic phosphates, phosphate ions, ammonium ions, silicate ions, transition metal carbonyls, and organic siloxanes or silicones. Common functional groups between the two species include alcohols and phenols, alkanes, alkenes, alkyl halides, methylene, acids, esters, ethers, aryl disulfides, cyanide and thiocyanate ions, carbonate ions, organic nitrates, nitrate ions, phosphate ions, and silicate ions. However, certain elements are specific to particular regions, such as alkynes. This study represents the first FTIR analysis conducted on the wing scales of P. aglea and A. terpsicore providing valuable insights into their chemical compositions.